ANALYSIS OF CRIMINAL LAW AND ISLAMIC CRIMINAL LAW ON THEFT WITH VIOLENCE (Comparative Study) - Muhammad Irwansyah Khadri (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Violent theft is one of the crimes that disturbs society, not only causing material losses but also deep psychological impacts on the victims. In Indonesia, this crime is regulated in the Criminal Code (KUHP), while in Islamic criminal law, violent theft is included in the category of hirabah. The method used in this study is a comparative study with a normative approach, which examines the legal provisions in the Criminal Code and Islamic criminal law in depth. The results of the study show that in Indonesian criminal law, violent theft is regulated in Article 365 of the Criminal Code which provides punishment based on the severity of the crime, ranging from imprisonment to the death penalty. Meanwhile, Islamic criminal law regulates violent theft in the context of hirabah, which provides more severe punishments, including amputating hands, feet, or even the death penalty, depending on the impact of the crime on society. A comparison of these two legal systems shows differences in the approach to justice and protection of society. Indonesian criminal law focuses more on protecting individuals, while Islamic criminal law emphasizes moral and social protection in order to maintain public order. Both legal systems aim to provide a deterrent effect, but in different ways in terms of punishment and enforcement of justice.